CORPUS LINGUISTICS AND ITS HISTORY: UNVEILING LANGUAGE THROUGH DATA - Farkhadova Zukhra; Fayziyeva Gulnoza (TADQIQOTLAR.UZ, 2024)
Corpus linguistics, the study of language based on large collections of real- world text and speech data, has revolutionized our understanding of how language functions. This article delves into the historical development of corpus linguistics, exploring its methodology, applications, advantages, and significant contributions to various fields.